AUTHENTIC ASSESSMENT IN EFL TEACHING AND LEARNING - Rama Dwika Herdiawan (ETERNAL (English Teaching Journal), 2018)
The assessment has been regarded as the crucial element in instructional process which involeved the teacher and students ini it. In addition, it requires a number of aspects which are concerned on authenticity of how students do the task performatively. Therefore, authentic assessment is necessarily selected in order to reach the goal or objectives of teaching and learning process which focused on real-world tasks. The five dimensional framework proposed by Gulikers et.al (2004) need to be employed inside the implementation of authentic assessment which covers at least: tasks, physical context, social context, result or form, and criteria. The framework represents how the students are assesses authentically as well performatively in order that there are innovative product and also perfomance created by the students particularly. Beacuse authenticity is crucially needed to model of assessment recently and it also represents the authentic outcomes that are totally obtained in the teaching and learning process. Authentic assessment is a new assessment paradigm which contributesto significant alternative towards the existence of traditional assessment practices which are still used by most of the teachers in any levels. Regarding the paradigm, assessment is a process which supports as well as improve students’ learning (focuses on enhancing their cognitive skills) instead of only assessing the teaching and learning process.